2018
DOI: 10.7589/2017-07-163
|View full text |Cite
|
Sign up to set email alerts
|

Usutu Virus Epizootic and Plasmodium Coinfection in Eurasian Blackbirds (Turdus merula) in Flanders, Belgium

Abstract: At the end of the summer of 2016, unusually high levels of mortality were detected in Passeriformes and Strigiformes in Flanders, Belgium, mainly in Eurasian Blackbirds ( Turdus merula). A passive surveillance program demonstrated a widespread Usutu virus outbreak and revealed a coinfection with Plasmodium in 99% of the dead passerine birds that were necropsied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 12 publications
5
26
0
Order By: Relevance
“…USUV is an emerging mosquito-borne flavivirus highly pathogenic to several wild bird species. After its emergence in Italy in 1996 (Weissenböck et al 2013), it has spread to several European countries, including Belgium in 2012, where it re-emerged in 2016 (Cadar et al 2016, Borm et al 2017, Garigliany et al 2017, Rouffaer et al 2018. In this study, we show that USUV infection in wild birds occurred in southern Belgium during the two subsequent years (2017)(2018).…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…USUV is an emerging mosquito-borne flavivirus highly pathogenic to several wild bird species. After its emergence in Italy in 1996 (Weissenböck et al 2013), it has spread to several European countries, including Belgium in 2012, where it re-emerged in 2016 (Cadar et al 2016, Borm et al 2017, Garigliany et al 2017, Rouffaer et al 2018. In this study, we show that USUV infection in wild birds occurred in southern Belgium during the two subsequent years (2017)(2018).…”
Section: Discussionsupporting
confidence: 53%
“…In Belgium, USUV infection was first detected in the Meuse Valley in a captive Eurasian bullfinch (Pyrrhula pyrrhula) and in a wild great spotted woodpecker (Dendrocopos major), both with neurological signs, in 2012 (Garigliany et al 2014). Four years later, high bird mortalities linked to USUV infection were documented all over the country (Cadar et al 2016, Borm et al 2017, Garigliany et al 2017, Rouffaer et al 2018, underlining the need for vigilance facing the reemergence and rapid spread of this virus.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to P. vaughani-infected birds, in which extensive tissue merogony was rarely detected, P. matutinum-infected birds were frequently affected by severe burdens of exo-erythrocytic stages, suggesting differences in virulence of these two lineages. Different strains of P. matutinum, which belongs to the subgenus Haemamoeba, have been reported to show variable levels of virulence in avian hosts [40], and previous studies already indicated that infection with LINN1 is associated with disease and mortalities [24][25][26]. In the present study numerous phanerozoites of P. matutinum LINN1 were particularly often detected in heart, lung, and brain of birds with high parasite burdens, similar to a previous report of fatal Plasmodium infection caused by this lineage [26].…”
Section: Discussionsupporting
confidence: 90%
“…The study showed that Eurasian blackbirds and song thrushes were frequently infected with haemosporidian parasites, particularly with Plasmodium spp., among which the lineages P. matutinum LINN1 (belonging to the subgenus Haemamoeba), and P. vaughani SYAT05 (subgenus Novyella) were predominant. High Plasmodium infection rates have been reported in these host species not only from Austria [25], but also from other localities in Europe [24,[35][36][37][38] and in thrushes introduced to New Zealand [39], suggesting that these birds are natural reservoir hosts for Plasmodium parasites. In contrast to the study by Dinhopl et al [25], which detected only single infections of Plasmodium spp., This investigation demonstrates that Eurasian blackbirds were regularly (up to 30%) affected by severe burdens of exo-erythrocytic stages of Plasmodium spp.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation